A Single Nucleotide Polymorphism in lptG Increases Tolerance to Bile Salts, Acid, and Staining of Calcofluor-Binding Polysaccharides in Salmonella enterica Serovar Typhimurium E40 - Wahlig, Taylor A.; Stanton, Eliot; Godfrey, Jared J.; Stasic, Andrew J.; Wong, Amy C. L.; Kaspar, Charles W. (Frontiers in Microbiology, 2021)
The outer membrane of Salmonella enterica plays an important role in combating stress encountered in the environment and hosts. The transport and insertion of LPS into the outer membrane involves lipopolysaccharide transport proteins (LptA-F) and mutations in the genes encoding for these proteins are often lethal or result in the transport of atypical LPS that can alter stress tolerance in bacteria. During studies of heterogeneity in bile salts tolerance, S. enterica serovar Typhimurium E40 was segregated into bile salts tolerant and sensitive cells by screening for growth in TSB with 10% bile salts. An isolate (E40V) with a bile salts MIC >20% was selected for further characterization. Whole-genome sequencing of E40 and E40V using Illumina and PacBio SMRT technologies revealed a nonsynonymous single nucleotide polymorphism (SNP) in lptG. Leucine at residue 26 in E40 was substituted with proline in E40V. In addition to growth in the presence of 10% bile salts, E40V was susceptible to novobiocin while E40 was not. Transcriptional analysis of E40 and E40V, in the absence of bile salts, revealed significantly greater (p<0.05) levels of transcript in three genes in E40V; yjbE (encoding for an extracellular polymeric substance production protein), yciE (encoding for a putative stress response protein), and an uncharacterized gene annotated as an acid shock protein precursor (ASPP). No transcripts of genes were present at a greater level in E40 compared to E40V. Corresponding with the greater level of these transcripts, E40V had greater survival at pH 3.35 and staining of Calcofluor-binding polysaccharide (CBPS). To confirm the SNP in lptG was associated with these phenotypes, strain E40E was engineered from E40 to encode for the variant form of LptG (L26P). E40E exhibited the same differences in gene transcripts and phenotypes as E40V, including susceptibility to novobiocin, confirming the SNP was responsible for these differences.